Investigating the Effectiveness of Supermarket Transmission Control Measures on the Spread of COVID-19 in the Presence of Super-Spreaders through Agent-Based Modelling - Mountford, Timothy (Department of Statistical Sciences, 2023)
An examination of the effectiveness of transmission control measures for COVID-19 in a supermarket setting, factoring for the inclusion of Super-Spreaders, must extend beyond the direct effects the control measure has on transmission in order to account for the indirect effects changes in human movement dynamics have on the spread of disease. The analysis makes use of Agent-Based Modelling simulation techniques to model changes in customer movement and disease transmission dynamics resulting from the isolated and combined implementation of COVID-19 transmission control measures. The bottom-up approach of agent-based modelling allows for the inclusion of heterogeneous, individual-level chances of infectiousness, compliance, and consumer behaviours, allowing for a more realistic representation of real-world behaviours. The model used for analysis is built entirely in the NetLogo environment, designed to be interactive, adaptable to user-varied inputs, and visually engaging. This allows for the model to adapt to changes in disease parameters and easily communicate model effects in a manner accessible to users in and out of the field. Control measures considered include: Vaccinations, Capacity Limiting, Social Distancing, Staff COVID-19 Testing, and the use of Sanitizers. Results indicate high levels of effectiveness for the use of Vaccinations at reducing transmission with minimal impact on customer dynamics. The results also highlight the negative effects changes in customer dynamics can have on transmission, indicated by increased shop-queue transmissions resulting from the use of Capacity Limiting or other measures slowing customer entrance to the shop. The positive effects of interactions between control measures are highlighted by the additional implementation of Social Distancing in reducing these increases. The implications of these findings involve the need to factor for changes in human movement dynamics when assessing the effectiveness of transmission control measures implemented in any environment. The findings further reinforce the benefits of implementing social distancing practises in conjunction with mechanisms that reduce the flow of movement, as well as the benefits of increased vaccination coverage in the population. Lastly, the findings provide an effective comparison of the control measures considered, allowing for the direct assessment of their implementation and the resulting effects on transmission and customer dynamics.